2014
DOI: 10.1371/journal.pone.0112357
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glutamate Supplementation Ameliorates Mycotoxin-Induced Abnormalities in the Intestinal Structure and Expression of Amino Acid Transporters in Young Pigs

Abstract: The purpose of this study was to investigate the hypothesis that dietary supplementation with glutamic acid has beneficial effects on growth performance, antioxidant system, intestinal morphology, serum amino acid profile and the gene expression of intestinal amino acid transporters in growing swine fed mold-contaminated feed. Fifteen pigs (Landrace×Large White) with a mean body weight (BW) of 55 kg were randomly divided into control group (basal feed), mycotoxin group (contaminated feed) and glutamate group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 72 publications
3
51
1
3
Order By: Relevance
“…However, amino acid flux in the serum can be affected by various factors (Wu et al 2014c). Previous studies have demonstrated that weaning stress or mycotoxin exposure changes serum profiles of amino acid in piglets, and the alterations can be ameliorated through dietary supplementation with Glu, Asp, or Arg (Duan et al 2014;Wu et al 2014a,b, c;2015a, b, c). Consistently, in the present study, intraperitoneal administration of H 2 O 2 reduced the concentration of most amino acids in the mesenteric, portal, and jugular veins, suggesting abnormal absorption and metabolism of amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, amino acid flux in the serum can be affected by various factors (Wu et al 2014c). Previous studies have demonstrated that weaning stress or mycotoxin exposure changes serum profiles of amino acid in piglets, and the alterations can be ameliorated through dietary supplementation with Glu, Asp, or Arg (Duan et al 2014;Wu et al 2014a,b, c;2015a, b, c). Consistently, in the present study, intraperitoneal administration of H 2 O 2 reduced the concentration of most amino acids in the mesenteric, portal, and jugular veins, suggesting abnormal absorption and metabolism of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Glu and Asp also serve as pivotal substrates for other biological active molecules, including the synthesis of glutamine, glutathione, proline, ornithine, and arginine (Ito et al 2012;Wu 2013b). Furthermore, Glu improves animal growth performance, regulate the metabolism of lipid and nitrogen to favor reduction in the whole-body white fat and growth of lean tissue (Boutry et al 2012;Chen et al 2014), beneficially modulates the gastrointestinal absorptive system (Zhang et al 2013), and enhances host anti-oxidative ability , and protects animals from damage caused by toxins exposure (Duan et al 2014;Wu et al 2014b). Asp has been reported to restore intestinal barrier and improve liver metabolism in piglets challenged with lipopolysaccharide (LPS) (Kang et al 2015;Pi et al 2014) possibly because of its contributions for the tricarboxylic acid cycle and the production of ATP (Russell and Taegtmeyer 1991).…”
Section: Introductionmentioning
confidence: 99%
“…We used the following protocol: (i) pre-denaturation (10 s at 95° C); (ii) amplification and quantification for 40 cycles (5s at 95° C, 20s at 60° C); (iii) melting curve analysis (60-99° C, at a heating rate of 0.1° C s -1 , with fluorescence measurements). The mRNA expression levels of target genes, in arbitrary units, were determined from the real-time PCR threshold cycle (Ct) in relation to β-actin, using the comparative Ct, via the 2 −∆∆Ct method [9][10][11].…”
Section: Chemical Analysismentioning
confidence: 99%
“…For weaned pigs, it has been suggested that the CP levels in their diets can be reduced by 2-3 points without affecting average daily gain (ADG) [4,6], feed efficiency, or gastrointestinal health when the diets are supplemented with AAs [7,8]. However, reductions exceeding 3 points have produced no effects on ADG, feed efficiency and the mRNA levels of digestive enzymes (including trypsinogen, chymotrypsin B, and dipeptidase-II and III) and AA transporters [2,4,[9][10][11][12][13], although these trends have not been observed in all studies [14][15][16]. These findings suggest that the reduction of dietary CP levels and supplementation with AAs may be an alternative method for decreasing N excretion and improving GIT digestive function while maintaining performance in young pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation